(untitled) (Research, Society and Development, 2020)
In Brazil and worldwide, an increase in breast cancer rates every year, so obese individuals have a risk of 1.5 to 3.5 more likely to develop cancer and obesity is also a risk factor for other cancers. . This article aims to analyze the association, prevalence and risk factors between obesity and breast cancer. This is an integrative literature review conducted through the databases of the Virtual Health Library (VHL), Scientific Electronic Library Online (SCIELO) and Latin American and Caribbean Health Sciences Literature (LILACS). After selecting twenty articles, only seven were part of the final sample. According to the results obtained, in the association between breast cancer and obesity, it was found in most studies that these are directly interconnected, which present pre-obesity and general obesity among women with breast cancer. Such results are closely linked to women undergoing postmenopausal treatment. Regarding prevalence, it is high among the population studied, risk factors indicate sedentary lifestyle, low physical activity and low knowledge about its benefits. The present study is limited to the association prevalence and risk factors between obesity and breast cancer. Given the above is evident the importance of studies such as these, since they contribute directly to scholars in the area, as well as to the literature.